PENGARUH PONDOK PESANTREN TERHADAP PEMBERDAYAAN EKONOMI PEREMPUAN DESA SEKITAR (Studi Pada Pondok Pesantren Modern Assaadah Desa Dahu Kecamatan Cikeusal Serang Banten) - Najmudin Najmudin; Ma’zumi Ma’zumi; Hasuri Hasuri (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2019)
This study aims to follow up and develop previous research by analyzing how much influence the Islamic boarding school has on the economic empowerment of women in surrounding villages. This study examines the influence of ijarah on women's economic empowerment, the effect of wakalah bil ujrah on women's economic empowerment and the influence of pesantren on women's economic empowerment. The objects of this study were the instructors of Islamic boarding schools, santri, BMT managers of pesantren and women from surrounding villages. This research uses quantitative methods using descriptive research and causal research. Data from the two variables above were analyzed using the SPSS v.19 program. the population in this study were santri, managers of BMT pesantren and women from surrounding villages. The data used in this study are primary data, through the distribution of questionnaires to 60 respondents consisting of santri, BMT pesantren managers and village women around Dahu village, Cikeusal sub-district, Serang Regency, Banten. Based on the results of data analysis, it was concluded that ijarah partially had a significant effect on women's economic empowerment. because the t value is greater than t table (7,937> 1,672) and the significance value is smaller than the α value (0,000 <0.05). wakalah bil ujrah partially has a significant effect on women's economic empowerment, because the value of t arithmetic is greater than t table (5,738> 1,672) and the significance value is smaller than the value of α (0,000 <0.05). Islamic boarding school has a positive and significant influence on the women economic empowerment in surrounding villages with a calculated F value greater than f table (233,491> 3.16) and a significance smaller than α (0,000 <0.05).